Recombination Marks the Evolutionary Dynamics of a Recently Endogenized Retrovirus. (4th September 2021) - Yang, Lei; Malhotra, Raunaq; Chikhi, Rayan; Elleder, Daniel; Kaiser, Theodora; Rong, Jesse; Medvedev, Paul; Poss, Mary
Abstract: All vertebrate genomes have been colonized by retroviruses along their evolutionary trajectory. Although endogenous retroviruses (ERVs) can contribute important physiological functions to contemporary hosts, such benefits are attributed to long-term coevolution of ERV and host because germline infections are rare and expansion is slow, and because the host effectively silences them. The genomes of several outbred species including mule deer ( Odocoileus hemionus ) are currently being colonized by ERVs, which provides an opportunity to study ERV dynamics at a time when few are fixed. We previously established the locus-specific distribution of cervid ERV (CrERV) in populations of mule deer. In this study, we determine the molecular evolutionary processes acting on CrERV at each locus in the context of phylogenetic origin, genome location, and population prevalence. A mule deer genome was de novo assembled from short- and long-insert mate pair reads and CrERV sequence generated at each locus. We report that CrERV composition and diversity have recently measurably increased by horizontal acquisition of a new retrovirus lineage. This new lineage has further expanded CrERV burden and CrERV genomic diversity by activating and recombining with existing CrERV. Resulting interlineage recombinants then endogenize and subsequently expand. CrERV loci are significantly closer to genes than expected if integration were random and gene proximity might explain the recent expansion of one recombinant CrERV lineage. Thus, in mule deer, retroviral colonization is a dynamic period in the molecular evolution of CrERV that also provides a burst of genomic diversity to the host population.